National early warning score (NEWS) – evaluation in surgery. Issue 3 (20th April 2015) - Neary, Peter M; Regan, Mark; Joyce, Myles J; McAnena, Oliver J; Callanan, Ian
Abstract : Purpose: – The purpose of this paper is to evaluate staff opinion on the impact of the National Early Warning Score (NEWS) system on surgical wards. In 2012, the NEWS system was introduced to Irish hospitals on a phased basis as part of a national clinical programme in acute care. Design/methodology/approach: – A modified established questionnaire was given to surgical nursing staff, surgical registrars, surgical senior house officers and surgical interns for completion six months following the introduction of the NEWS system into an Irish university hospital. Findings: – Amongst the registrars, 89 per cent were unsure if the NEWS system would improve patient care. Less than half of staff felt consultants and surgical registrars supported the NEWS system. Staff felt the NEWS did not correlate well clinically with patients within the first 24 hours (Day zero) post-operatively. Furthermore, 78-85 per cent of nurses and registrars felt a rapid response team should be part of the escalation protocol. Research limitations/implications: – Senior medical staff were not convinced that the NEWS system may improve patient care. Appropriate audit proving a beneficial impact of the NEWS system on patient outcome may be essential in gaining support from senior doctors. Deficiencies with the system were also observed including the absence of a rapid response team as part of the escalation protocol and a lack of concordance of the NEWS in patients Day zero post-operatively. These issues should be addressed moving forward. Originality/value: – Appropriate audit of the impact of the NEWS system on patient outcome may be pertinent to obtain the support from senior doctors. Deficiencies with the system were also observed including the absence of a rapid response team as part of the escalation protocol and a lack of concordance of the NEWS in patients Day zero post-operatively. These issues should be addressed moving forward.